2020
DOI: 10.1186/s12864-020-07276-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of three gonadal development stages reveals potential genes involved in gametogenesis of the fluted giant clam (Tridacna squamosa)

Abstract: Background Gonad development and differentiation is an essential function for all sexually reproducing species, and many aspects of these developmental processes are highly conserved among the metazoa. However, the mechanisms underlying gonad development and gametogenesis remain unclear in Tridacna squamosa, a large-size bivalve of great ecological value. They are protandrous simultaneous hermaphrodites, with the male gonad maturing first, eventually followed by the female gonads. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 99 publications
(107 reference statements)
2
21
0
Order By: Relevance
“…But just like other Tssk members, Tssk5 have the conserved lysine residue ( Figure 2 ) that is involved in ATP binding. Moreover, Tssk5 has the same expression pattern in male testis as other Tssk members in the bay scallop A. irradians (this study), Yesso scallop P. yessoensis , and clam Tridacna squamosa ( Li et al, 2020 ). Considering the presence of key amino acids and the similar expression pattern with other Tssk members, we assume that Tssk5 may be a functional gene in mollusks.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…But just like other Tssk members, Tssk5 have the conserved lysine residue ( Figure 2 ) that is involved in ATP binding. Moreover, Tssk5 has the same expression pattern in male testis as other Tssk members in the bay scallop A. irradians (this study), Yesso scallop P. yessoensis , and clam Tridacna squamosa ( Li et al, 2020 ). Considering the presence of key amino acids and the similar expression pattern with other Tssk members, we assume that Tssk5 may be a functional gene in mollusks.…”
Section: Discussionsupporting
confidence: 58%
“…For a precise reproductive control during the breeding process, a comprehensive understanding of molecular mechanism underlying gametogenesis is required. Massive screening of reproduction-specific genes in scallop Argopecten purpuratus ( Boutet et al, 2008 ), mussel Mytilus edulis ( Ciocan et al, 2011 ), and clam Tridacna squamosa ( Li et al, 2020 ) revealed that Tssk genes are involved in sexual maturation of testis. However, only Tssk1 has been cloned and characterized in mollusks.…”
Section: Introductionmentioning
confidence: 99%
“…In the sequential hermaphrodites, a potential sex-determining pathway containing SoxH, Dmrt, and FoxL2 has been proposed in the Pacific oyster Crassostrea gigas ( Zhang et al, 2014 ), and Fem1-like, Dmrt, and FoxL2 are considered as key sex-determining genes in the pearl oyster Pinctada margaritifera ( Teaniniuraitemoana et al, 2014 , 2015 ). Recent studies reported the transcriptome sequencing of two simultaneous hermaphroditic bivalves, lion-paw scallop Nodipecten subnodosus and giant clam Tridacna squamosa , from which several sex-related genes were identified ( Galindo-Torres et al, 2018 ; Li et al, 2020 ). But as yet, research on the sexual development of simultaneous hermaphroditic mollusks is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 87 candidate genes (1095) reportedly involved the gonad development, sex differences, and sex determination ( Zhang et al, 2014 ; Yatsu et al, 2016 ; Li et al, 2020 ; Zhang et al, 2020 ; Broqurad et al, 2021 ) were present in the full-length gonad transcriptome of 30-month-old H. schlegelii ( Supplementary Table S5 ). Four major sex determination-related genes in mollusks, dmrt-like , sox9 , wnt4 , and fem1 were present in the full-length gonad transcriptome.…”
Section: Resultsmentioning
confidence: 99%
“…Hermaphroditism occurs during gonadal development of H. schlegelii as in other bivalves, such as Arconaia lanceolata ( Wu et al, 2018 ), Pinctada Margaritifera ( Teaniniuraitemoana et al, 2014 ), Tridacna squamosa ( Li et al, 2020 ), and Crassostrea gigas ( Broquard et al, 2021 ). Hermaphrodite bivalves act as egg-producing females or sperm-producing males at least once in their life cycle.…”
Section: Introductionmentioning
confidence: 99%